2019
DOI: 10.1590/1413-81232018249.31402017
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da redistribuição das causas mal definidas de óbito sobre a taxa de mortalidade por câncer de mama no Brasil

Abstract: Resumo A relevância do câncer de mama para as mulheres tem impulsionado pesquisas sobre a mortalidade desta doença. Todavia, estes estudos estão sujeitos aos problemas gerados pelos óbitos oriundos de causas mal definidas (CMD). A fim de evidenciar as possíveis distorções causadas pelas CMD em estudos que avaliam a mortalidade, foram calculadas taxas de mortalidade, padronizadas por faixa etária, com e sem correção para CMD, para os anos de 1990, 2000 e 2010. Feito isso, foram estimados modelos de regressão co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
1
2
0
2
Order By: Relevance
“…Those produced in the last 10 years generally showed an increase in mortality between the 1980s and 2000s followed by stability or a slight increase, with variations among regions. These rates decreased in the southeastern and southern regions and increased in the northern and northeastern regions [3,17,[20][21][22][23]. In addition to these findings, the study by Meira et al [15] used the same APC method applied in this study, and the results indicated higher rates for older age groups and a nonlinear pattern in the rates of birth cohorts, with recent cohorts showing an increased risk for cancer deaths.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Those produced in the last 10 years generally showed an increase in mortality between the 1980s and 2000s followed by stability or a slight increase, with variations among regions. These rates decreased in the southeastern and southern regions and increased in the northern and northeastern regions [3,17,[20][21][22][23]. In addition to these findings, the study by Meira et al [15] used the same APC method applied in this study, and the results indicated higher rates for older age groups and a nonlinear pattern in the rates of birth cohorts, with recent cohorts showing an increased risk for cancer deaths.…”
Section: Discussionsupporting
confidence: 50%
“…The underreporting of breast cancer deaths was corrected considering deaths from ill-defined causes using the methodology proposed by the World Health Organization (WHO) [16], as exemplified by Couto et al [17]. This method recommends the redistribution of ill-defined causes by a two-step procedure.…”
Section: Methodsmentioning
confidence: 99%
“…In an evaluation conducted in the early 2020s, Brazilian mortality data were classified in the same quality category as those of European countries such as Germany, France, Italy, Spain, Switzerland, Sweden, Norway, Denmark, Belgium and the Netherlands [ 59 ]. Due to improvements in the quality of death records in Brazil in the last two decades, there has been not only a significant increase in the coverage of mortality records [ 60 ] but also a gradual decrease in the percentage of ill-defined causes [ 61 ]. For cancer, the impact of mortality from ill-defined causes tends to be even lower.…”
Section: Discussionmentioning
confidence: 99%
“…As causas mal definidas (R00-R99) e as outras causas também são tratadas como categorias separadas das demais na análise. Ainda que a redistribuição proporcional dos óbitos com causa mal declarada sobre os demais grupos traria melhora na análise do volume de óbitos, ela pode introduzir viés, por subestimar determinados grupos de causa, especialmente em grupos etários específicos (COUTO et al, 2019;RAMSAY et al, 2020). As informações faltantes de idade e sexo foram distribuídas proporcionalmente de acordo com a estrutura observada para os óbitos com idade e sexo declarados.…”
Section: Dadosunclassified